Profil Unsur Tanah Jarang Granitoid Klabat di Pulau Bangka dengan Analisis Aktivasi Neutron - Widana, Kurnia Setiawan; Priadi, Bambang; Handayani, Yustina Tri (BRIN Publishing, 2014)
Neutron Activation Analysis (NAA) is a powerful geochemical analysis with advantages which are nondestructive and involves multi-elements. NAA technique applied for qualitative and quantitative analyses on Klabat granitic rocks that distributes and compose the geology of Bangka Island. There are 27 samples analyzed which aims to determine the content of rare earth elements, which will be applied in petrotectonic of Klabat granitoid. Rare Earth Elements (REE) which analyzed, namely La, Ce, Nd, Sm, E, Gd, Tb, Yb, and Lu. All of the samples irradiated in the Centre of Multipurpose Reactor